2010
DOI: 10.1016/j.mvr.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Improved assessment of laser-induced choroidal neovascularization

Abstract: The primary objective of this study was to develop and evaluate new methods of analyzing laser-induced choroidal neovascularization (CNV), in order to make recommendations for improving the reporting of experimental CNV in the literature. Six laser burns of sufficient power to rupture Bruch's membrane were concentrically placed in each eye of 18 adult Norway rats. Eyes received intravitreal injections of either triamcinolone acetonide, ketorolac, or balanced salt solution (BSS). Fluorescein angiography (FA) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…This indicates the potential of topically applied anti-VEGF DARPin to treat chorioretinal neovascularization.
Fig. 6The effect of DARPin eye-drops on rat choroidal neovascularization (CNV) in comparison to Triamcinolon (positive control, ivt) [45] or PBS (buffer control, ivt). a Comparison of mean CNV lesion size of the different study groups.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the potential of topically applied anti-VEGF DARPin to treat chorioretinal neovascularization.
Fig. 6The effect of DARPin eye-drops on rat choroidal neovascularization (CNV) in comparison to Triamcinolon (positive control, ivt) [45] or PBS (buffer control, ivt). a Comparison of mean CNV lesion size of the different study groups.
…”
Section: Resultsmentioning
confidence: 99%
“…The effect of DARPin eye-drops on rat choroidal neovascularization (CNV) in comparison to Triamcinolon (positive control, ivt) [45] or PBS (buffer control, ivt). a Comparison of mean CNV lesion size of the different study groups.…”
Section: Resultsmentioning
confidence: 99%
“…Toma et al (2010) previously evaluated several edge detection techniques for measuring experimental CNV area from FA images using commercial software. The techniques had some level of automation; however, retinal specialists were still needed to outline the lesion or the user was required to manually adjust the threshold level for each image until the irrelevant microvasculature surrounding the lesion disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14][15] Although studies of the pathogenesis and treatment of AMD have been delayed by lacking of ideal animal models, 16 laserinduced CNV rodent models are commonly used to study CNV in wet AMD. [17][18][19][20] Moreover, our previous study has shown that the Wnt signaling pathway is activated in very low-density lipoprotein receptor (VLDLR) knockout (KO) mice, a genetic animal model of subretinal neovascularization (NV). 21 The present study investigated the role of the Wnt signaling pathway in laser-induced CNV and explored therapeutic potential of a blocker of Wnt signaling in laser-induced CNV and VLDLR KO models.…”
mentioning
confidence: 99%